2020
DOI: 10.1155/2020/8107478
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic and Predictive Value of Cadherin 11 for Patients with Gastric Cancer and Its Correlation with Tumor Microenvironment: Results from Microarray Analysis

Abstract: Gastric cancer is a disease characterized by inflammation, and epithelial-to-mesenchymal transition (EMT) and tumor-associated macrophages (TAMs) both play a vital role in epithelial-driven malignancy. In the present study, we performed an integrated bioinformatics analysis of transcriptome data from multiple databases of gastric cancer patients and worked on a biomarker for evaluating tumor prognosis. We found that cadherin 11 (CDH11) is highly expressed not only in gastric cancer tissues but also in EMT mole… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 65 publications
1
5
0
Order By: Relevance
“…The AJCC pathological tumor stage and nuclear grade are commonly used for prognostic diagnoses in patients with RCC. Our statistical analysis of clinicopathological features in patients with RCC showed a positive correlation between the CDH11 methylation status and the tumor stage or nuclear grade, which was consistent with the conclusions obtained from gastric cancer and non-muscle invasive bladder cancer [28][29][30][31] . Our data in the subsequently functional trails also showed that ectopic expression of CDH11 gene inhibited the proliferation, migration and invasion in RCC cell lines.…”
Section: Discussionsupporting
confidence: 89%
“…The AJCC pathological tumor stage and nuclear grade are commonly used for prognostic diagnoses in patients with RCC. Our statistical analysis of clinicopathological features in patients with RCC showed a positive correlation between the CDH11 methylation status and the tumor stage or nuclear grade, which was consistent with the conclusions obtained from gastric cancer and non-muscle invasive bladder cancer [28][29][30][31] . Our data in the subsequently functional trails also showed that ectopic expression of CDH11 gene inhibited the proliferation, migration and invasion in RCC cell lines.…”
Section: Discussionsupporting
confidence: 89%
“…Kaplan-Meier analysis and the log-rank test were applied to determine the survival curves. Correlations between key genes, infiltrating cell types, and gene markers were established by Spearman's correlation, and correlation strength was classified according to the absolute value of the partial correlation coefficient as follows: 0.00-0.19 "a negligible correlation"; 0.20-0.39 "a weak correlation"; 0.40-0.59 "a moderate correlation"; 0.60-0.79 "a strong correlation"; and 0.80-1.0 "a very strong correlation" [40,41]. The results were considered to have statistical significance when P < 0:05.…”
Section: Analyses Of Key Gene-tumor Microenvironment (Tme)mentioning
confidence: 99%
“…Two molecular modules were identified using MCODE, the most important of which contained 11 key genes (RRM2, NDC80, ECT2, CCNB1, ASPM, CDK1, PRC1, KIF20A, DTL, TOP2A, and PBK), as visualized in Figure 4(b), which also revealed that this molecular module plays an important role in the process of hepatocarcinogenesis. HCV-related HCC (53) vs. HCV-related hepatitis (40) HBV-related HCC (39) vs.…”
Section: Ppi Network and Molecularmentioning
confidence: 99%
“…CDH11 is known as a transmembrane protein mediating cellular adhesion and a hallmark of mesenchymal phenotype that is broadly expressed in multiple cell types undergoing EMT including breast [ 17 , 18 , 20 , 21 ], prostate [ 22 , 23 ], brain [ 40 ], renal [ 24 ], bone [ 25 ], bladder [ 41 ], ovary [ 42 ] and gastric [ 43 , 44 ] cancer cells. Although some studies reported that CDH11 is frequently methylated and silenced in certain types of cancers [ 45 , 46 , 47 ], cumulative emerging evidence suggests that CDH11 may play a critical role in promoting tumorigenesis and metastasis in breast cancer.…”
Section: Discussionmentioning
confidence: 99%